Impact of Increase on the Inter Household Transfers on the Economy in Indonesia - Wisnu Winardi; Hadi Susanto; Kadim Martana (Pusat Penelitian, Badan Keahlian DPR RI, 2017)
In these recent years Indonesian economy has gained a robust growth coupled with declining unemployment rate and poverty rate. However, the achievement is still flawed by persistent problem of income distribution. As a large country with heterogeneous population that bound by strong cultural and religious values, Indonesia has underlying factors to improve the situation. One of the important factors is inter household transfers. This research aims at identifying economy-wide impacts of increased inter household transfers as a reflection of better social care on some aspects of national economy. This research utilized CGE model with 2008 Indonesia Social Accounting Matrix as database and analyzed the model with the assumption of long term period of simulation result. Results suggest that increased inter household transfers brought about positive changes in all household income, improved government income, fixing price level as well as distributional income. Furthermore, the shocks cause adjustment in the national economic structure on expenditure, particularly on household consumption and investment. Share of household consumption to GDP is expected to slightly decrease, while that investment is to increase. These findings indicate that the increased household transfers are worth conducting from the view point of social aspects as well as economic aspects.